Zebrafish as an emerging model to study estrogen receptors in neural development - Boueid, Marie-José; El-Hage, Océane; Schumacher, Michael; Degerny, Cindy; Tawk, Marcel (Frontiers in Endocrinology, 2023)
Estrogens induce several regulatory signals in the nervous system that are mainly mediated through estrogen receptors (ERs). ERs are largely expressed in the nervous system, yet the importance of ERs to neural development has only been elucidated over the last decades. Accumulating evidence shows a fundamental role for estrogens in the development of the central and peripheral nervous systems, hence, the contribution of ERs to neural function is now a growing area of research. The conservation of the structure of the ERs and their response to estrogens make the zebrafish an interesting model to dissect the role of estrogens in the nervous system. In this review, we highlight major findings of ER signaling in embryonic zebrafish neural development and compare the similarities and differences to research in rodents. We also discuss how the recent generation of zebrafish ER mutants, coupled with the availability of several transgenic reporter lines, its amenability to pharmacological studies and in vivo live imaging, could help us explore ER function in embryonic neural development.